Shabbir Akhtar on Muslims, Christians and British society: An appraisal and Christian response - Herbert, David (Islam and Christian-Muslim relations, 1993)
An attempt will be made here to engage with the work of Shabbir Akhtar, whose stance as a theological modernist and Muslim fundamentalist represents one possible direction for the development of British Islam. Several points will be made which look toward constructive ways of negotiating with differences in a pluralist society. These include a recognition of the role of implicit theology in shaping our opinions, and the adoption of non-foundationalist philosophical positions. In response to Akhtar's criticisms of Christian theologies of power I call for a closer analysis of power and its operation, and for more energy to be devoted to alternative methods of persuasion and conflict resolution to the use of violence, observing that British Muslims are already becoming familiar with such methods, as the burning of The Satanic Verses illustrates.